MEDIA SENTIMENT AND STOCK PRICES: ANALYSING TEMPORAL DYNAMICS AND PREDICTIVE RELATIONSHIPS IN TESLA AND META - Laura Čigileičikaitė; Gabrielė Gailiūtė; Jekaterina Kartašova (Agora International Journal of Economical Sciences)
The study investigates the relationship between media sentiment and stock price fluctuations. Using quantitative techniques, the research examines data from Tesla and Meta from 2019 to 2024. Headlines and adjusted stock prices were processed into monthly averages to reduce noise, enabling statistical analysis through cross-correlation and Granger causality tests. The results indicate a link between sentiment and stock prices, suggesting that sentiment may have some predictive capability for stock price movements. The research underscores the importance of addressing media sentiment in financial decision-making.